Notkun og kostnaður lyfja sem notuð eru við iðraólgu - Linda Björk Ólafsdóttir; Hallgrímur Guðjónsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: To study the use and value of drugs used for irritable bowel syndrome (IBS) in Iceland and compare with other Nordic countries. Methods: A retrospective study was performed. Information on use and value of IBS-drugs was obtained from the Ministry of Health. Five years period 1989-1993, was investigated. Mebeverine, butylscopolamine and clidine, all the drugs in the A03 group were studied. Furthermore it was estimated that in 50% of cases ispaghula fibers were used for IBS. The use was measured in daily defined doses (DDD) per 1000 inhabitants and the value was calculated according to wholesaleprice from pharmacies on the 1st of November 1993. Information from the Nordic statistics on medicine was utilized to compare Iceland with other Nordic countries for the period 1990-1992. Results: In Iceland the administration and expenses of IBS-medications decreased significantly during the investigated period. The use decreased from 7.96 DDD to 4.57 DDD, from the beginning to the end of the period. The total drug cost decreased of 45%, from 50 to 28 millions ISK. The use of A03-drugs is much more common in Iceland, than in Denmark, Norway and Sweden. IBS-drugs expenses are by far the highest in Iceland, twice to three times higher than in other Nordic countries. Conclusion: The administration and expenses of IBS-drugs in Iceland is substantial, but it is decreasing. IBS-drug therapy in Iceland is more common and expensive than in other Nordic countries. Tilgangur: Að kanna notkun og kostnað lyfja sem notuð eru við iðraólgu (irritabel bowel syndrome) á Íslandi og bera saman við önnur Norðurlönd. Efniviður og aðferðir: Könnunin var afturskyggn. Upplýsingar um notkun og kostnað á iðraólgulyfjum voru fengnar frá heilbrigðisráðuneytinu. Fimm ára tímabil (1989-1993) var valið. Iðraólgulyf (A03 lyfjaflokkur) voru talin vera; mebeverín, bútýlskópólamín og klídín. Auk þess sem áætlað var að í helmingi tilvika væru ...